Boosting the NIR reflective properties of perylene organic coatings with thermoplastic hollow microspheres: Optical and structural properties by a multi-technique approach. (1st March 2020) - Minei, Pierpaolo; Lessi, Marco; Contiero, Luca; Borsacchi, Silvia; Martini, Francesca; Ruggeri, Giacomo; Geppi, Marco; Bellina, Fabio; Pucci, Andrea
Highlights: Paliogen black was utilized as cool organic pigment. Waterborne acrylic coatings were obtained on white and black substrates. Thermoplastic hollow microspheres were utilized to boost NIR reflectivity. SR measurements allowed to determine the cooling features of the prepared coatings. Abstract: This study reports for the first time the use of thermoplastic hollow microspheres (THM) in combination with a perylene bisimide pigment (Paliogen® Black L0086 (P-black)) for the preparation of acrylic coatings with near-infrared (NIR) reflecting and cooling characteristics. VIS-NIR spectra showed that P-black solid dispersions provide reflectance values in agreement with the P-black content and its crystalline nature. The introduction of THM with average diameter of 25 ± 5 μm with the same weight content of P-black did not substantially affect the crystalline nature of the pigment within the organic coating even if a decreasing of the long range order in the molecular packing of the perylene chromophores emerged from XRD and solid-state NMR investigations. Noteworthy, the addition of the THM successfully contributed in the exponential raising of the solar reflectance (SR) of coated black substrates, i.e. reaching up to the 22% at the highest organic layer thickness of 255 μm. The effective combination between THM and P-black was well reflected on the temperature of the back side of the coated surface after irradiation with a solar simulator, i.e. with a maximum cooling effect of about 6 °C.